2019
DOI: 10.1002/jeab.546
|View full text |Cite
|
Sign up to set email alerts
|

Further evaluation of a nonsequential approach to studying operant renewal

Abstract: Basic‐laboratory assessments of renewal may inform clinical efforts to maintain reduction of severe destructive behavior when clients transition between contexts. The contextual changes arranged during standard renewal procedures, however, do not necessarily align with those that clients experience during outpatient therapy. More specifically, clients transition between clinical (associated with extinction for target behavior) and home/community (associated with reinforcement for target behavior) contexts duri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 50 publications
0
10
1
Order By: Relevance
“…Craig, Sullivan, Browning, DeRosa, and Roane show that rats intermittently exposed to reinforcement for a target behavior in the previous training context (i.e., Context A) during extinction of that response in a different context (i.e., Context B) show less renewal when tested in a different context (i.e., Context C) than rats not experiencing such intermittent exposure to Context A reinforcement. This result stands in contrast to previous work by these authors (Craig, Sullivan, & Roane, ) showing that such intermittent exposure to reinforcement to Context A instead increases ABA renewal in a similar procedure. The authors suggest that alternating between contexts associated with reinforcement and extinction during treatment may offer a clinical strategy for reducing renewal of problem behavior in novel contexts.…”
Section: Renewalcontrasting
confidence: 99%
“…Craig, Sullivan, Browning, DeRosa, and Roane show that rats intermittently exposed to reinforcement for a target behavior in the previous training context (i.e., Context A) during extinction of that response in a different context (i.e., Context B) show less renewal when tested in a different context (i.e., Context C) than rats not experiencing such intermittent exposure to Context A reinforcement. This result stands in contrast to previous work by these authors (Craig, Sullivan, & Roane, ) showing that such intermittent exposure to reinforcement to Context A instead increases ABA renewal in a similar procedure. The authors suggest that alternating between contexts associated with reinforcement and extinction during treatment may offer a clinical strategy for reducing renewal of problem behavior in novel contexts.…”
Section: Renewalcontrasting
confidence: 99%
“…Rats were approximately 12 months old at the beginning of the experiment and had no previous experience with resurgence preparations. They did, however, have a previous history with reinforcement and extinction across various contextual manipulations (see Craig, Sullivan, Browning et al, ; Craig, Sullivan, & Roane, ). Rats were pair‐housed in a temperature‐ and humidity‐controlled colony room with a 12:12 hr light/dark cycle.…”
Section: Methodsmentioning
confidence: 99%
“…Before beginning Phase 2, rats were assigned to either the DRA with extinction plus NCR group ( n = 5) or to the DRA without extinction group ( n = 5). Given that past research has suggested baseline response rates predict the magnitude of relapse (e.g., Craig, Sullivan, & Roane, ; Podlesnik et al, ; Sweeney & Shahan, ), rats were matched such that the mean rates of target‐lever pressing during the final three sessions of Phase 1 did not differ between groups. Sessions of Phase 2 began similarly to Phase 1 in that both levers were inserted into the chamber with the stimulus light positioned above the target lever illuminated.…”
Section: Methodsmentioning
confidence: 99%
“…To the extent that these (and other) differences were observed across studies (see Falligant et al., 2021), it is unclear if these inconsistent findings are related to differences in the clinical contexts in which treatments were developed and implemented (i.e., outpatient vs. inpatient settings) and reflect additional variation between settings that warrant investigation (e.g., different functional classes of behavior, nonsequential renewal effects, etc. ; Craig et al., 2019; Sullivan et al., 2018).…”
Section: Introductionmentioning
confidence: 99%
“… Also note that, in the context of outpatient‐based treatment of severe problem behavior, these renewal phenomenon may be further defined specifically as nonsequential renewal effects (see Craig et al., 2019). …”
mentioning
confidence: 99%